Post effects associated with SARS-CoV-2 vaccination among health care workers in Pakistan - Warda Furqan; Afnan Naeem; Javaid Usman; Ayesha Ellahi; Fahad Ahmed; Ali Raza Ahmed (International Journal of Public Health Science (IJPHS), 2022)
The COVID-19 pandemic has witnessed the rapid development of vaccines produced simultaneously form various countries. However, these vaccines were shrouded by a set of myths ranging from serious effects to change of human DNA. Pakistan was one of the countries to start vaccination early and the front-line workers were first to be vaccinated. We undertook to study the vaccinated health care workers for the post effects of vaccines they received. The methodology adopted was through a structured questionnaire comprising 12 questions covering almost all the possible post effects. This was circulated among health care workers of Pak-Emirates Military hospital and Army Medical College/ National University of Medical Sciences, Rawalpindi, Pakistan. Fever was the most frequently encountered post effect, followed closely by pain at site of injection, headache and fatigue. There was a strong association between age and post effects of vaccination. No life threatening or serious side effects were experienced by health are workers indicating that benefits of vaccine outweigh its adverse effects especially with emergence of new variants. No participant required hospitalization following immunization. Therefore, vaccination against SARS-CoV-2 should be carried out on priority basis in order to avoid severe COVID-19 infection.